T-cells of invasive candidiasis patients show patterns of T-cell-exhaustion suggesting checkpoint blockade as treatment option. Issue 2 (February 2022) - Mellinghoff, Sibylle C.; Thelen, Martin; Bruns, Christiane; Garcia-Marquez, Maria; Hartmann, Pia; Lammertz, Tatjana; Lehmann, Jonas; Nowag, Angela; Stemler, Jannik; Wennhold, Kerstin; Cornely, Oliver A.; von Bergwelt-Baildon, Michael S.; et al.
Summary: Objective: Recent data imply that strengthening host immunity by checkpoint inhibition improves outcome in invasive fungal infections (IFI), particularly in candidiasis. Methods: To assess T-cell exhaustion in this context, we compared peripheral blood mononuclear cells (PBMCs) and serum samples of patients with invasive Candida albicans infection (IC, n  = 21) to PBMCs or tumor-infiltrating lymphocytes (TILs) from cancer patients ( n  = 14) and PBMCs of healthy controls ( n  = 20). Type and differentiation of lymphocytes and expression of 29 immune-regulatory molecules were analyzed by flow cytometry. C. albicans specific responses were assessed by FluoroSpot ( n  = 8) and antibody measurement ( n  = 14). Results: Fractions and phenotypes of lymphocyte subsets in PBMCs of IC patients were similar compared to PBMCs of controls, while they were different in TILs. PBMCs of patients with IC showed increased expression of immune-checkpoint molecules. The pattern of upregulated molecules was similar to TILs, but not present in PBMCs of control cancer patients. Fractions of T-cells expressing PD-1 and TIGIT were higher in IC patients that died. FluoroSpot analysis showed a Candida -specific IFN-y or IL-2 response in 5/8 patients, enhanced by addition of nivolumab in vitro . Conclusions: Together with preclinical data and preliminary evidence of clinical efficacy in mucormycosis, our results support clinical evaluation of immune-checkpoint inhibition in IFI treatment. Trial registration: NCT04533087; retrospectively registered on August 31, 2020